One-step synthesis of IrOx-decorated ultrathin NiFe LDH nanosheets for efficient oxygen evolution reaction. Issue 77 (28th August 2020) - Liu, Depei; Du, Yu; Li, Taozhu; Zhang, Hehe; Liu, Duanduan; Zhang, Weining; Tang, Huang; Hou, Yanghui; Li, Jingsha; Yan, Shicheng; Yu, Tao; Zou, Zhigang
Abstract : IrO x decoration promotes intrinsic OER activity of NiFe LDH by increasing active site and electric conductivity. Abstract : The oxygen evolution reaction (OER) is a vital proton donor for various clean energy technologies. Here, we synthesized IrO x -decorated ultrathin NiFe-LDH nanosheets (thickness 1–2 nm) by a one-step co-precipitation method. The IrO x was uniformly dispersed on the surface of ultrathin NiFe-LDH nanosheets, greatly increasing the active sites and the electric conductivity for NiFe-LDH. As a result, the IrO x /U-NiFe-LDH exhibited excellent OER performance with a low overpotential (236 mV) and a Tafel slope (74.3 mA dec −1 ).